Inclusive sustainable intensification of agriculture in West Bengal, India: policy and institutional approaches. Issue 1 (2nd January 2020) - Reddy, V. Ratna; Chiranjeevi, T.; Syme, Geoff
ABSTRACT: This article assesses the potential and constraints for existing policies and institutions in the context of inclusive sustainable agricultural intensification (SAI). SAI is being promoted and adopted with positive impacts on crop yields and natural resources across a number of countries. This study is based on a review of studies and analysis using secondary as well as primary data from two villages in West Bengal, India. There is little evidence that the study region is in any way moving towards SAI in the real sense of the term. Lack of awareness and pressing income needs are driving farmers towards unsustainable practices. The main constraint is that there is no comprehensive policy frame to promote SAI although there are individual programmes and policies. While there are programmes to promote organic farming and natural farming, most policies are in favour of promoting chemical fertilizers rather than organic inputs. Although there are number of formal and informal institutions, they are not effective in promoting SAI, as they are linked programmatically and function in silos. It is argued that there is a need for synergy among various formal and informal institutions with Panchayati Raj institutions at village level playing the central role.